Sedimentation of self-propelled Janus colloids: polarization and pressure - Felix Ginot; Alexandre Solon; Yariv Kafri; Christophe Ybert; Julien Tailleur; Cecile Cottin-Bizonne (New Journal of Physics, 2018)
We study experimentally—using Janus colloids—and theoretically—using Active Brownian Particles—the sedimentation of dilute active colloids. We first confirm the existence of an exponential density profile. We show experimentally the emergence of a polarized steady state outside the effective equilibrium regime, i.e. when the sedimentation speed v _s is not much smaller than the propulsion speed v _0 . The experimental distribution of polarization is very well described by the theoretical prediction with no fitting parameter. We then discuss and compare three expressions which have been proposed to measure the pressure of sedimenting particles: the weight of particles above a given height, the flux of momentum and active impulse, and the force density measured by pressure gauges.